Implication of phylogenetic systematics of Rodent-Borne hantaviruses allows understanding of their distribution - Vincent Herbreteau (2018)
Hantaviruses' distribution is reassessed after performing a cladistic analysis on 93 strains isolated from rodents, and one used as outgroup: Thottapalayam isolated from a shrew. While most hantaviruses found in wild animals were collected in northern Asia, Europe, North America, and South America, only Thottapalayam and Thailand were found in South and Southeastern Asia. Thottapalayam is highly divergent from the other known hantaviruses and may represent the emerging tip of a different lineage. Serological surveys carried out to detect evidence of Hantavirus in human populations revealed positive samples not only in West and Central Africa but also in Thailand, with a first case recently confirmed. This suggests that Hantaan-related viruses may infect humans out of their well-documented range. Thus, if rodents are probably the primary reservoir, other mammals may be involved in the cycle of hantaviruses. Additional work is needed out of the traditional areas where hantaviruses have been recorded. New viruses, different hosts, and different human syndromes may be discovered in the future mainly in Southeastern Asia and in Africa where Muridae rodents are present and highly diversified. © 2006 New York Academy of Sciences.